Pengaruh Laba Akuntansi, Ukuran Perusahaan, dan Pertumbuhan Penjualan terhadap Return Saham pada PT Polychem Indonesia Tbk Periode 2015-2024 - Septina Nuraini; Adji Widodo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to examine the effect of Accounting Profit, Firm Size, and Sales Growth on Stock Returns at PT Polychem Indonesia Tbk during the 2015–2024 period, both partially and simultaneously. The research employed a quantitative approach using secondary data derived from the company’s financial statements throughout the study period. Data analysis techniques included descriptive statistics, classical assumption tests, multiple linear regression analysis, coefficient of determination (R²), and hypothesis testing using t-tests and F-tests. The results show that partially Accounting Profit does not have a significant effect on Stock Returns (t-value −0.255 < t-table 2.447; significance 0.807 > 0.05). Firm Size also does not significantly affect Stock Returns (t-value 1.046 < t-table 2.447; significance 0.336 > 0.05). Similarly, Sales Growth does not have a significant effect on Stock Returns (t-value 1.519 < t-table 2.447; significance 0.180 > 0.05). Simultaneously, the three independent variables do not significantly influence Stock Returns (F-value 1.278 < F-table 4.76; significance 0.364 > 0.05). The Adjusted R² value of 0.085 indicates that Accounting Profit, Firm Size, and Sales Growth collectively explain only 8.5% of the variation in Stock Returns, while the remaining 91.5% is influenced by other factors outside the model, including macroeconomic conditions, government policies, market sentiment, and industry dynamics. Keywords: accounting profit; firm size; sales growth; stock return